DETERMINING THE QUANTITIES OF WASTE STREAMS: DETERMINING THE QUANTITIES OF WASTE STREAMS - Takova, Iva (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
In this research, we examine and distinguish the waste that is landfilled at the local level, this is the process by which unwanted and unnecessary waste is disposed of. We can distinguish them by defining and evaluating them properly. There is a law that states that municipal programs for waste management are sectoral programs and are an integral part of municipal programs for environmental protection. We will also consider the objectives guaranteeing the achievement of the general objective of the Plan. We will consider the equations by which the amount of household waste generated is determined.